Extension of the seaport life cycle (SLC) by utilising existing inland capacity for current and future trade preparation - Jagan Jeevan; C. K. Yeng; M. R. Othman (Asian Journal of Shipping and Logistics (AJSL), 2021)
This paper explores the structure of the seaport life cycle (SLC) of Malaysian container seaports to restructure the seaport development plan. Quadratic regression analysis is proposed to stratify the life cycle stages of seaports through the quantification of throughput volume, and forecast future growth patterns of seaports. The findings show that Port Klang, Penang Port, PTP and Kuantan Port are experiencing the growth stage in their seaport life cycles, while Johor Port is standing at the decline stage of the seaport life cycle. Penang Port and Port Klang are expected to continue growing until 2050. Meanwhile, PTP, Johor Port and Kuantan Port have entered the maturity stage in 2018 and are expected to move into the declining stage by 2050. This paper provides significant evidence about the need to establish a link between seaports and dry ports, and develop a symbiotic strategy to prolong the life cycle of seaports. Academically, this paper provides significant literature on Malaysian seaport cycles, which may be utilised for seaport development plans to cater to the demands of the domestic and global market.
Keywords: 650; Malaysian seaports; Seaport life cycle; Quadratic regression analysis; Dry ports